The influence of knowledge and health service in the usage of oral rehydration salts in diarrhea management for children under 5 years; case study in Balikpapan, Indonesia - Tri Murti; Muhammad Hanafiah Juni; Hejar Abdul Rahman; Salmiah M.S (Jurnal EduHealth, 2024)
Oral Rehydration Salts (ORS) solution can contribute to a substantial reduction in infant deaths from diarrhea. However, factors affecting the use of ORS is not known at Balikpapan City, Indonesia. This study aims to establish the determinants of ORS use in children under-five years with diarrhea in Balikpapan City, Indonesia. To examine the Influence of Knowledge and Health Service in the usage oral rehydration salts in diarrheal management for children under 5 years among mothers attending health clinics in Balikpapan. A cross sectional study was done based on 3 health clinics. Four hundred three mothers with children who have diarrhea 2 weeks episode and are under the age of 5 years. Definition ORS used sachet package and salt sugar solution. Data were collected using structured questionnaires, including demographic information, knowledge about diarrhea, health service factors and cost in health facility the management of diarrhea. The prevalence of mothers used ORS for the management of diarrhea was only 68.7%. Factors associated with ORS used were knowledgeable mothers about danger signs of diarrhea (adj. OR: 170.49, 95% CI: 41.38, 702.46); obtain of ORS from public health facilities (adj. OR: 22.7, 95% CI: 6.93, 74.41). Health seeking behavior, knowledge, source and mode of obtaining ORS significantly increases ORS solution use in children under-five with diarrhea in Balikpapan District.